THE INFLUENCE OF THE ATTRACTIVENESS OF PROMOTIONS AND PRODUCT DESIGN ON THE DECISION TO PURCHASE THE HONDA ALL NEW BRIO SATYA - Kairupan, Daniel Joel Immanuel; Laksono, Deni Budi (Jurnal Ilmiah Manajemen dan Bisnis (JIMBis), 2024)
This research aims to analyze the influence of promotional attractiveness and product design on consumer purchasing decisions. The influence of these factors on consumer behavior has become a major concern in modern marketing studies, as they have a significant role in shaping purchasing preferences. In this context, a quantitative approach is used to collect data from respondents consisting of active consumers in various industrial sectors. This research draws samples from a consumer population representing a variety of demographic backgrounds and product preferences. Survey methods are used to collect primary data related to consumer perceptions about the attractiveness of promotions and product designs as well as their purchasing decisions. Data analysis was carried out using multiple linear regression techniques to identify the relationship between the variables studied. The analysis tool uses SPSS 26. The research results show that both promotional appeal and product design have a significant influence on consumer purchasing decisions. These findings provide valuable insights for marketing practitioners to design effective strategies to increase sales and consumer satisfaction.